Peculiarities of the user interface of a legal document drafting system - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 2008)
The objective of legal document drafting system is both facilitating the work of legislative drafters and improving the quality of laws. However, currently almost all legislative bodies use general purpose wordprocessing software for the drafting of legal documents, and internet browsers for seaching documents. This is because legal drafting systems have too little facilities so far and are rather difficult for use. The paper discusses specific features of the user interface of a legal document drafting system. It is focused on the functionality of the user interface. User groups are identified as legislative drafters, legislators, experts, system administrators, and knowledge engineers. Usability requirements for these groups are described in the paper.
Keywords: legal knowledge base; legal engineering; legal document drafting system